FAKTOR-FAKTOR YANG MEMPENGARUHI KESEHATAN MENTAL IBU HAMIL - Cory Habibah Lisiana Putri; Gabriela Nadya Maharani; Sari Rahmawati; Wahyudi (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
Pregnant women are at a higher risk of experiencing mental health disorders, such as depression, anxiety, and self-harming behaviors. These risks may worsen due to various factors, including spousal support, maternal age, parity, and social support. Pregnancy accompanied by maternal mental health issues can become a serious concern. Therefore, it is important to understand the factors that influence this condition. This review uses a Literature Review method, beginning with the identification of relevant journal articles using the keywords “mental health” and “pregnant women.” Article searches were conducted in both Indonesian and English through databases such as Google Scholar and PubMed, limited to publications from 2021–2025. A total of five articles were included in this review three national and two international which were then analyzed thoroughly. The results of the analysis indicate that support from the husband is the most influential factor, having a greater impact than other factors such as parity, maternal age, and social support from the surrounding environment. These factors can affect the mental health of mothers during pregnancy. It is expected that this issue will receive attention from midwives as healthcare providers as well as from the government, so that improvements can be made in the future to enhance maternal psychological well-being, allowing pregnancies to proceed healthily for all expectant mothers.